A DFT Study of the Hydrogen Bonded Structures of Pyruvic Acid–Water Complexes - Hammami, Ferid; Issaoui, Noureddine (Frontiers in Physics, 2022)
The molecular geometries of the possible conformations of pyruvic acid-water complexes (PA-(H2O)n = 1- 4) have been fully optimized at DFT/B3LYP/6-311G ++ (d, p) levels of calculation. Among several optimized molecular clusters, we present here the most stable molecular arrangements obtained when one, two, three, and four water molecules are hydrogen bonded to a central pyruvic acid molecule. Appropriate topological and geometrical parameters are considered as primary indicators of H-bond strength. AIM analysis shows that pyruvic acid can form a ring structure with water and the molecular structures are stabilized by both strong O-H...O and C-H...O hydrogen bonds. In large clusters, classical O-H...O hydrogen bonds still exist between water molecules and a cage-like structure is built around some parts of the central molecule of pyruvic acid.